2023
DOI: 10.3389/fspas.2023.1107605
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive response of thermospheric cooling to ICME and CIR-driven geomagnetic storms

Abstract: The temporal response of thermospheric CO2 and NO cooling emissions is investigated during ICME and CIR-driven geomagnetic storms by using data from the SABER instrument onboard the TIMED, GRACE, and DMSP satellites. The superposed epoch analysis reveals that the cooling emissions experience a strong enhancement and quick recovery to pre-event value within 3–4 days during CME storms. Whereas, it shows slower recovery that lasts for more than 6–7 days during CIR-driven storms. We performed detailed study of NO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…A detailed description of this specific event was provided by Piersanti et al (2022). We suspect that cooling effects (Mlynczak et al, 2014;Knipp et al, 2017;Bag et al, 2023) have occurred, which subsequently reduced the increase of the neutral mass density during this specific event. In Oliveira and Zesta (2019) the authors have quantified The second event we highlight is the most prominent example on our validation list.…”
Section: Validation Of Forecastingmentioning
confidence: 93%
“…A detailed description of this specific event was provided by Piersanti et al (2022). We suspect that cooling effects (Mlynczak et al, 2014;Knipp et al, 2017;Bag et al, 2023) have occurred, which subsequently reduced the increase of the neutral mass density during this specific event. In Oliveira and Zesta (2019) the authors have quantified The second event we highlight is the most prominent example on our validation list.…”
Section: Validation Of Forecastingmentioning
confidence: 93%
“…The effectiveness of the NO cooling emission and its relation with Joule heating rate still remains elusive. Since the NO 5.3 μm cooling emission controls the thermospheric temperature and density during geomagnetic active periods and accounts for about 80% of Joule heating energy (Lu et al, 2010) and also dissipates significant amount of energy (Bag, 2018a(Bag, , 2018bBag et al, 2020Bag et al, , 2023aBag et al, , 2023bMlynczak et al, 2003), the plan of the present study is to examine the temporal response of NO cooling emission to the Joule heating rate during magnetic active periods by utilizing the EISCAT incoherent scatter radar measurements and TIMED/SABER observations. This study is divided into four sections.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, solar wind energy deposition, particularly during extreme geomagnetic storms, causes large-scale global perturbations in the MIT system including the thermospheric energetics and dynamics through the processes of Joule heating and energetic particle precipitation (Sinnhuber, 2012). Several studies report on the impacts of the extreme geomagnetic storms on the MIT system (Lu et al, 1988;Vichare et al, 2005;Sutton et al, 2005;Krauss et al, 2015Krauss et al, , 2018Bag et al, 2014, 2021, 2023a, b, Bag., 2018Bharti et al, 2018;Oliveira et al, 2020;and references therein). Horvath and Lovell (2010) observed the large-scale propagation of ionospheric disturbances and their impact on the equatorial ionization anomaly during extreme geomagnetic storms.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing 15 years (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) of TIMED/SABER observations, Tang et al (2017) showed that the NO cooling flux at the polar region is about three times larger than the equatorial value. The NO cooling emission also undergoes a significant enhancement during geomagnetic storm periods due to its sensitivity to Joule heating and particle precipitation (Lu et al, 2010;Mlynczak et al, 2003Mlynczak et al, , 2010Knipp et al, 2013Knipp et al, , 2017Bag., 2018;Bharti et al, 2018;Bag et al, 2021Bag et al, , 2023aLi et al, 2018;and references therein). In addition, earlier studies show that NO cooling emission can contribute to the overcooling of the thermosphere and density overdamping due to the early and excessive production of NO density (Lei et al, 2012;Knipp et al, 2017).…”
Section: Introductionmentioning
confidence: 99%